ROBOT PENJELAJAH BERODA AUTONOMOUS - Joni Fat Fat; Riski Sanderson Sanderson (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
The wheeled robot design consists of various modules with their own functionalities. We chosethe components based on theirs specification, autonomous functionality, and in theirs prices. We assembledthese components as modules. The modules in this design are power supply module, processing modulewhich is used ATMega 328 microcontroller, distance sensor module, line sensor module, wirelesscommunication module, motor driver module and actuator module which is used DC motor. Systemperformance indicated with: Able to follow square, triangle, synes conture and stopping ability. Experimentshawed that all of the modules worked as design. The robot could navigate according to contoursautonomously. We tested by using a display module. We gave inputs and then feeded to processing modulethrough bluetooth. From the experiment, it can be concluded that the robot which was using wall followingmethod could be controlled well. The PID controller performed well so the navigation could be stable. Thestable condition was achieved under 3 seconds. But the performance criteria had not been achieved becausethe maximum overshoot was 41.2% which was far from the limit of 10%.